Little Hands - Jood Hamdallah; Saleh Sawalha (My University, 2025)
This project “Little Hands” presents a digital child care platform designed to connect parents with trusted caregivers, child support specialists, and experts through a single, easy-to-use app. It helps parents find and book the most suitable support based on their specific needs, offering access to essential services such as babysitting, special needs care, and expert consultations—whether at home, school, or online. The application was developed using Flutter for the frontend (user interface) and Node.js for the backend (server side). It features dedicated user interfaces for both families and caregivers, with a secure login and registration system. Caregivers can register, subscribe to the platform, and choose a specific role (e.g., babysitter, expert, or special needs supporter). Parents in turn, can search for matching caregivers, browse detailed profiles, check availability, read reviews, exchange messages, and book sessions for the desired service directly through the app. Main features include guided booking flows, personalized caregiver matching, integrated feedback and rating systems, real-time messaging, notifications, and calendar-based scheduling. In addition to live services, the platform also offers access to valuable children-related educational content shared by expert caregivers, helping parents stay informed and supported beyond the sessions. By incorporating essential child care services in one platform, Little Hands offers parents a reliable, easy, and convenient way to find professional support for their children’s health, development, and well-being.